A Korean Folktale, Kongjee-Patjee: an Analysis of the Concept of Binary Opposition - Kim Jang Gyem (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
This article presents an analysis of a Korean folktale, Kongjee-Patjee. The theory used in this paper to analyze the folktale is the concept of Binary Opposition. In addition, Vladimir Propp’s approach toward folk tales is also used to analyze the meaning of symbols and the roles of characters in the story, and the position of this folk tale in Korean society. The differences and similarities of the Kongjee-Patjee story from other folk tales are discussed. Attempts are also made to analyze the meanings of the symbols in the story by analyzing the animal characters and their roles within Korean society and examine these animal symbols in understanding the culture of the Koreans. The contradiction between the protagonist and the antagonist also attracts our attention to look at the construction of the story and the messages in the story.